Muscle wasting as an independent predictor of survival in patients with chronic heart failure. Issue 5 (6th August 2020) - von Haehling, Stephan; Garfias Macedo, Tania; Valentova, Miroslava; Anker, Markus S.; Ebner, Nicole; Bekfani, Tarek; Haarmann, Helge; Schefold, Joerg C.; Lainscak, Mitja; Cleland, John G. F.; Doehner, Wolfram; Hasenfuss, Gerd; et al.
Abstract: Background: Skeletal muscle wasting is an extremely common feature in patients with heart failure, affecting approximately 20% of ambulatory patients with even higher values during acute decompensation. Its occurrence is associated with reduced exercise capacity, muscle strength, and quality of life. We sought to investigate if the presence of muscle wasting carries prognostic information. Methods: Two hundred sixty‐eight ambulatory patients with heart failure (age 67.1 ± 10.9 years, New York Heart Association class 2.3 ± 0.6, left ventricular ejection fraction 39 ± 13.3%, and 21% female) were prospectively enrolled as part of the Studies Investigating Co‐morbidities Aggravating Heart Failure. Muscle wasting as assessed using dual‐energy X‐ray absorptiometry was present in 47 patients (17.5%). Results: During a mean follow‐up of 67.2 ± 28.02 months, 95 patients (35.4%) died from any cause. After adjusting for age, New York Heart Association class, left ventricular ejection fraction, creatinine, N‐terminal pro‐B‐type natriuretic peptide, and iron deficiency, muscle wasting remained an independent predictor of death (hazard ratio 1.80, 95% confidence interval 1.01–3.19, P = 0.04). This effect was more pronounced in patients with heart failure with reduced than in heart failure with preserved ejection fraction. Conclusions: Muscle wasting is an independent predictor of death in ambulatory patients with heart failure. Clinical trials are needed to identify treatment approaches to this co‐morbidity.